2003
DOI: 10.1111/j.1432-2277.2003.tb00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diltiazem administration and cyclosporine levels on the incidence of acute rejection in heart transplant patients

Abstract: To identify the clinical factors associated with acute rejection (AR) in the first year after heart transplantation (HT), we analysed 112 patients. All patients received OKT3 and standard triple-drug therapy. We analysed the following variables to determine their relationship with AR: age and gender, panel-reactive antibodies, HLA-DR mismatch, use of Sandimmune vs Neoral, diltiazem administration, and cyclosporine levels in week 2 and months 1, 2, and 3 after HT. Fifty-two patients had no AR and 49 had at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Early studies showed that the use of diltiazem reduced the narrowing of coronary vascular lumen in transplant patients, especially during the first year posttransplant [22]. In addition to their antihypertensive properties, CCB use has been linked to reduce the risk of acute rejection partly by increasing CNI's levels [23].…”
Section: Andandmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies showed that the use of diltiazem reduced the narrowing of coronary vascular lumen in transplant patients, especially during the first year posttransplant [22]. In addition to their antihypertensive properties, CCB use has been linked to reduce the risk of acute rejection partly by increasing CNI's levels [23].…”
Section: Andandmentioning
confidence: 99%
“…Moreover, hypertension is a common adverse effect of steroids and calcineurin inhibitors due to their ability to alter vascular tone and activate the sympathetic system, resulting in an increased tendency for salt and water retention through their impact on the distal convoluted tubule [38]. While key to managing hypertension involves appropriately weaning steroids and adjusting calcineurin inhibitors, CCB and thiazides diuretics are commonly used antihypertensives [21 ▪▪ ,23].…”
Section: Practical Approach To Post-heart Transplant Hypertensionmentioning
confidence: 99%
“…Some transplant centers have used the drug interactions between cyclosporine and drugs such as ketoconazole, fluconazole, or diltiazem for their cyclosporine-sparing effects. 37,38 Although controversial, this practice substantially reduces the cyclosporine acquisition cost and in some cases allows for once-daily dosing. The safety and efficacy of such regimens have been established on a limited basis.…”
Section: Drug Interactionsmentioning
confidence: 99%